(2x-5)(3x)=125

Simple and best practice solution for (2x-5)(3x)=125 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-5)(3x)=125 equation:


Simplifying
(2x + -5)(3x) = 125

Reorder the terms:
(-5 + 2x)(3x) = 125

Remove parenthesis around (3x)
(-5 + 2x) * 3x = 125

Reorder the terms for easier multiplication:
3x(-5 + 2x) = 125
(-5 * 3x + 2x * 3x) = 125
(-15x + 6x2) = 125

Solving
-15x + 6x2 = 125

Solving for variable 'x'.

Reorder the terms:
-125 + -15x + 6x2 = 125 + -125

Combine like terms: 125 + -125 = 0
-125 + -15x + 6x2 = 0

Begin completing the square.  Divide all terms by
6 the coefficient of the squared term: 

Divide each side by '6'.
-20.83333333 + -2.5x + x2 = 0

Move the constant term to the right:

Add '20.83333333' to each side of the equation.
-20.83333333 + -2.5x + 20.83333333 + x2 = 0 + 20.83333333

Reorder the terms:
-20.83333333 + 20.83333333 + -2.5x + x2 = 0 + 20.83333333

Combine like terms: -20.83333333 + 20.83333333 = 0.00000000
0.00000000 + -2.5x + x2 = 0 + 20.83333333
-2.5x + x2 = 0 + 20.83333333

Combine like terms: 0 + 20.83333333 = 20.83333333
-2.5x + x2 = 20.83333333

The x term is -2.5x.  Take half its coefficient (-1.25).
Square it (1.5625) and add it to both sides.

Add '1.5625' to each side of the equation.
-2.5x + 1.5625 + x2 = 20.83333333 + 1.5625

Reorder the terms:
1.5625 + -2.5x + x2 = 20.83333333 + 1.5625

Combine like terms: 20.83333333 + 1.5625 = 22.39583333
1.5625 + -2.5x + x2 = 22.39583333

Factor a perfect square on the left side:
(x + -1.25)(x + -1.25) = 22.39583333

Calculate the square root of the right side: 4.732423621

Break this problem into two subproblems by setting 
(x + -1.25) equal to 4.732423621 and -4.732423621.

Subproblem 1

x + -1.25 = 4.732423621 Simplifying x + -1.25 = 4.732423621 Reorder the terms: -1.25 + x = 4.732423621 Solving -1.25 + x = 4.732423621 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.25' to each side of the equation. -1.25 + 1.25 + x = 4.732423621 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + x = 4.732423621 + 1.25 x = 4.732423621 + 1.25 Combine like terms: 4.732423621 + 1.25 = 5.982423621 x = 5.982423621 Simplifying x = 5.982423621

Subproblem 2

x + -1.25 = -4.732423621 Simplifying x + -1.25 = -4.732423621 Reorder the terms: -1.25 + x = -4.732423621 Solving -1.25 + x = -4.732423621 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.25' to each side of the equation. -1.25 + 1.25 + x = -4.732423621 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + x = -4.732423621 + 1.25 x = -4.732423621 + 1.25 Combine like terms: -4.732423621 + 1.25 = -3.482423621 x = -3.482423621 Simplifying x = -3.482423621

Solution

The solution to the problem is based on the solutions from the subproblems. x = {5.982423621, -3.482423621}

See similar equations:

| 0.36x-x^3= | | 2x^2-20x-64=0 | | ln(8)+ln(b)-ln(4)=ln(12) | | z+1=z-3 | | G=7b(r-8) | | 77-3X=-56-7X | | 2X+12=-36-6X | | 1-w-w^2=0 | | 3x+p=q | | 4w^4+9m^2= | | 747-60h=747 | | 1x^2-17x+42=0 | | (x+6)(x+2)=(2x-2)(x+4) | | x+5=(x+5) | | 2X+20=6X+11 | | x+5=(x+5)2 | | 747-60h=300 | | d=a+b+cforb | | 5=x+25x+25 | | 0.65x+0.05(16-x)=0.10(-28) | | (x+6)(x-3)=(2x+5)(x-3) | | x+25x=5 | | 0.16x-x^3= | | x=25x+20 | | (3x+8)(x-4)=12x+32 | | 2.564x=12.46104 | | 3y+3x=-3y+17x | | 3x+3y=-3x+17y | | 9n^8-16p^2= | | 2(-1)-5= | | -2.7=3.3-3y | | 9x^2+24xy+16y^2= |

Equations solver categories